Removal of nickel from aqueous solution using electric arc furnace slag - Mohammed Yusuf (2012)
Electric Arc Furnace (EAF) slag is a major abundant by-product in Malaysia steel industry. It has potential to be used as low cost adsorbent for heavy metal removal from waste water. The aim of this study was to examine the potential capability of an electric arc furnace slag on the removal of nickel in both batch and fixed bed column system. The ability of electric arc furnace slag (EAFS) to remove nickel was investigated in term of adsorption kinetics and isotherm as well as the adsorption capacity in batch and fixed column system. Moreover, the effects of pH, adsorbent dosage, initial metal ion concentration and particle size were determined in batch process using artificial neural network (ANN) and the effect of bed height and flow rate were examined in the fixed bed column system. From the experimental result obtained, it is found that the EAFS adsorption kinetics obeyed the pseudo-second-order kinetic model with fairly high correlation coefficient. The adsorption process obeyed the Langmuir isotherm model and the maximum uptake of nickel (II) from the solution is 160.9 mg/g. The optimum pH and temperature was observed to be at pH 8 and 28oC respectively for the maximum removal of nickel. The equilibrium time was determined at 9 hours for the nickel and it was observed that the metal adsorption capacity decreased as the particle size of the EAFS increased from 0.5 mm to 3 mm. The bed depth service time (BDST) model fitted well with the experimental data where the service time decreased accordingly as the bed depth decreased. Thomas model also described well the adsorption behavior of the effect of flow rate on adsorption capacity and break through curves. From the study, it was concluded that the EAFS, can be an efficient low cost adsorbent to remove heavy metals particularly nickel from industrial waste water.